2015
DOI: 10.1016/j.jchf.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and Continuous-Flow Left Ventricular Assist Devices

Abstract: Echocardiography is the most used imaging modality in the growing population of patients with advanced heart failure undergoing continuous-flow, durable mechanical circulatory support. However, no guidelines for the use of echocardiography in this population exist, evidence for core applications is limited and conflicting, and newer centrifugal-flow devices have been subject to minimal study. As a first step toward addressing these deficits, this review summarizes the evidence and expert opinion for the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 71 publications
0
41
0
2
Order By: Relevance
“…4 The "waterfall" artifact associated with the HeartWare (HeartWare International Inc., Framingham, MA) is an analogous example of this. 5 On meticulous retrospective review of the patient's 15 imaging studies performed since arrival at the authors' institution until upgrade to the CentriMag biventricular assist device, 1 of 11 TTE studies was found to have possible evidence of AR on hospital day 13, roughly 2 weeks after the Impella 5.0 implant. Significant color Doppler artifact induced by the Impella device likely obscured any existing AR jet (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…4 The "waterfall" artifact associated with the HeartWare (HeartWare International Inc., Framingham, MA) is an analogous example of this. 5 On meticulous retrospective review of the patient's 15 imaging studies performed since arrival at the authors' institution until upgrade to the CentriMag biventricular assist device, 1 of 11 TTE studies was found to have possible evidence of AR on hospital day 13, roughly 2 weeks after the Impella 5.0 implant. Significant color Doppler artifact induced by the Impella device likely obscured any existing AR jet (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…It stands to reason that the commonly used semiquantitative assessment of AR may lead to underestimation of the true severity of AR, because it discounts that the regurgitant flow is not limited to diastole. Clear guidelines on the core applications of echocardiography in patients with cf-LVADs are lacking [21]. Recently, this knowledge gap has been somewhat reduced by recognition that simultaneous input from right-side heart catheterization and echocardiography provide better estimates of aortic valve regurgitant fraction than conventional echocardiographic measurements alone [22] in this patient population.…”
Section: Commentmentioning
confidence: 99%
“…Related studies have identified that the blood pump inlet cannula influences the rate of cerebrovascular adverse events [10–12]. The blood pump inlet cannula is usually inserted into the left ventricle (LV) apex [13,14]. Javid Fatullayev’s study revealed that the positioning of the inflow cannula and the size of the pump pocket were shown to putatively contribute to thrombosis [15].…”
Section: Introductionmentioning
confidence: 99%